-7x-5(5x+14)=-6

Simple and best practice solution for -7x-5(5x+14)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-5(5x+14)=-6 equation:


Simplifying
-7x + -5(5x + 14) = -6

Reorder the terms:
-7x + -5(14 + 5x) = -6
-7x + (14 * -5 + 5x * -5) = -6
-7x + (-70 + -25x) = -6

Reorder the terms:
-70 + -7x + -25x = -6

Combine like terms: -7x + -25x = -32x
-70 + -32x = -6

Solving
-70 + -32x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '70' to each side of the equation.
-70 + 70 + -32x = -6 + 70

Combine like terms: -70 + 70 = 0
0 + -32x = -6 + 70
-32x = -6 + 70

Combine like terms: -6 + 70 = 64
-32x = 64

Divide each side by '-32'.
x = -2

Simplifying
x = -2

See similar equations:

| (4b^2)^-1/2 | | S^2+8s-5=0 | | x-(x*0.55)=13548479*0.55 | | 1.5×45/2 | | 7y-3x=2 | | 1/3×3(5x-14)=18×1/3 | | x-(x*.2)=15668730*0.2 | | x-(x*0.2)=100*0.2 | | 5t-13=7 | | x-x*0.2=100*0.2 | | 6e+2=10e+4e | | 6x-5y=-60 | | 7x-16+5x-3+4x+7=180 | | (4x-1)(2x+4)=0 | | 11x-5+9x+1+3x=180 | | 7.3=p+0.1 | | p+1.5=1.6 | | 5.5=r-7.1 | | f(x)=x^4-4x^3-2x^2+12x+9 | | 3(4x+3)=-0(-x+2) | | Ll2c-7/3=5 | | 6x+4(-3x+31)=58 | | (16-2x)(12-2x)=0 | | 2logx-3logy+2logxy= | | -28=x-46 | | C=20n | | (2y)-x=50 | | t+(-36)=-43 | | 2y-x=50 | | 38=x+16 | | 21-2h=13 | | (y-8)/7=(-9) |

Equations solver categories